How do you use the quadratic formula to find both solutions to the quadratic equation #(2y - 3) (y + 1) = 5#?

1 Answer
Jul 6, 2015

Answer:

Multiply out and rearrange into the form #ay^2+by+c = 0# then use the quadratic formula to find:

#y = (1+-sqrt(65))/4#

Explanation:

#5 = (2y-3)(y+1) = 2y^2-y-3#

Subtract #5# from both sides to get:

#2y^2-y-8 = 0#

This is of the form #ay^2+by+c = 0#

with #a=2#, #b=-1# and #c=-8#

This has solutions given by the quadratic formula:

#y = (-b +-sqrt(b^2-4ac))/(2a)#

#=(1+-sqrt((-1)^2-(4xx2xx-8)))/(2*2)#

#=(1+-sqrt(65))/4#